Antineutrophil cytoplasmic antibodies in patients with tuberculosis - Hussein, Sahib; Ismael, May; Abdulmajeed, Nahlah (Iraqi Journal of Science, 2023)
Tuberculosis is caused by Mycobacterium tuberculosis; it is considered as one of the most common, infectious diseases and major causes of morbidity and mortality worldwide. A prospective study was conducted to obtain more clarification about the impact of causative agent and its treatment to enhance autoantibodies production such as ANCA and BPI which used as diagnostic markers for several diseases, and to provide further insight into the classical risk factors (age and sex).Seventy patients with tuberculosis involved in this study, 35 of them were untreated and 35 with treatment administration these patients were attending to directorate of general health national reference laboratory in Baghdad during the period between November/ 2012 and March/ 2013 as well as 20 apparently healthy volunteers as control group. Their ages ranged between 11-70 years.The present study revealed that most patients at the third decades of age; male were affected more than female (1.8:1).Estimation of serum ANCA were done by indirect immunofluorescent (IIF) whereas BPI measured by enzyme linked immune sorbent assay (ELISA) and comparing with healthy control (H.C) group.The current study revealed that high significant increasing of ANCA and BPI in tuberculosis patients 71.43% and 15.71% respectively as compared with H.C 15% and 0% respectively. Also the data of the research showed significant differences of ANCA between untreated group 82.85% and treated group 60%. As well as our results showed differences of BPI percentage between, before treatment group 17.14% and after treatment group 14.28% but non-significant (p> 0.05).These results showed that Mycobacterium tuberculosis plays pivotal role in stimulation autoantibodies production. In contrast to our study on the treatment influences had yielded controversial results. Clinically, present of positive ANCA in patients with TB confused the diagnosis of Wegener's granulomatosis as many of the clinical features of this disease eg. Haemoptysis and pulmonary infiltrate may also be found in patients with TB.